Wave like signatures in aerosol optical depth and associated radiative impacts over the central Himalayan region. (October 2015) - Shukla, K.K.; Phanikumar, D.V.; Kumar, K. Niranjan; Reddy, Kishore; Kotamarthi, V.R.; Newsom, Rob K.; Ouarda, Taha B.M.J.
Abstract: Doppler Lidar and Multi-Filter Rotating Shadowband Radiometer (MFRSR) observations are utilized to show wave like signatures in aerosol optical depth (AOD) during daytime boundary layer evolution over the Himalayan region. Fourier analysis depicted 60–80 min periods dominant during afternoon hours, implying that observed modulations could be plausible reason for the AOD forenoon–afternoon asymmetry which was previously reported. Inclusion of wave amplitude in diurnal variation of aerosol radiative forcing estimates showed ~40% additional warming in the atmosphere relative to mean AOD. The present observations emphasize the importance of wave induced variations in AOD and radiation budget over the site. Highlights: Wave like signatures in aerosol optical depth over the central Himalayan region. 60–80 min period oscillations dominant during afternoon hours. Inclusion of wave amplitude in diurnal variation of aerosol radiative forcing. Additional warming (cooling) in the atmosphere (surface) due to wave dynamics.